Gonadotropin-Releasing Hormone and Its Role in the Enteric Nervous System - Ohlsson, Bodil (Frontiers in Endocrinology, 2017)
Gonadotropin-releasing hormone (GnRH), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) orchestrate the reproduction cycle and regulate the sex steroid secretion from the gonads. In mammals, GnRH1 is secreted as a hormone from the hypothalamus, whereas both GnRH1 and GnRH2 are present as neurotransmitters/peptides in a variety of tissues, where the peptides exert many different effects. mRNA coding for GnRH1 and GnRH2 have been described in the human gastrointestinal tract, and GnRH has been found in both submucosal and myenteric neurons. mRNA coding for GnRH and the fully expressed peptide have been found in rat enteric neurons by some researchers but not by others. mRNA coding for GnRH receptors, but not the fully expressed receptor, has been found in one rat study. GnRH influences gastrointestinal motility and secretion. GnRH analogs are clinically used in the treatment of sex hormone-dependent diseases, i.e., endometriosis and malignancies, and as pretreatment for in vitro fertilization (IVF). Reduced numbers of enteric neurons and IgM antibodies against GnRH and progonadoliberin-2 (precursor of GnRH2) have been observed after such treatment, with the clinical picture of gastrointestinal dysmotility. Similarly, a rat model of enteric neurodegeneration has been developed after administration of the GnRH analog buserelin. Serum IgM antibodies against GnRH1, progonadoliberin-2, and GnRH receptors have been described in patients with signs and symptoms of gastrointestinal dysmotility and/or autonomic dysfunction, such as irritable bowel syndrome (IBS), enteric dysmotility, diabetes mellitus, and primary Sjögren´s syndrome. Thus, apart from regulation of reproduction and sex hormone secretion, GnRH also constitute a part of ENS and its functions during physiological and pathological conditions. This review aimed to describe the role of GnRH in the enteric nervous system (ENS).